Transforming Encounters and Critical Reflection: African Thought, Critical Theory, and Liberation Theology in Dialogue - Anné Hendrik Verhoef (Ed.); Justin Sands (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
ca. 200 words; this text will present the book in all promotional forms (e.g. flyers). Please describe the book in straightforward and consumer-friendly terms. [Transforming Encounters and Critical Reflection: African Thought, Critical Theory and Liberation Theology in Dialogue is an interdisciplinary exploration of Western ideologies and their impact on Southern African cultures and societies. It brings together scholars whose expertise resides within the subdisciplines of decolonial and African thought, liberation theology, and postmodern philosophy to explore the intersectionality of Western hedgemony. Although broad in approach, each author s contribution coalesces around an extended meditation on the question of what is liberation for Southern Africa (and the global south writ large) and from what is it being liberated.]
English
Keywords: Liberation Theology; Transformation; Critical Theory; Contextual Theology; African Philosophy; Decolonization; African Thought; Postcolonial Studies